Disaster Prevention and Risk Reduction Education Implementation in Special Education Schools in Indonesia: Teachers Challenges, Strategies, and Recommendations - Cabatay*, Mulina Madlangbayan; Gonzales, Heidi Baraan (Universitas Syiah Kuala, 2024)
Indonesia adopted the Comprehensive School Safety framework to increase the resilience of all its citizens to disaster. During a disaster, children with special needs and disabilities (SEND) are more likely to be abandoned. Hence, this research, targets to determine special education teachers disaster education plans and strategies, and the challenges they encountered in implementing Satuan Pendidikan Aman Bencana (SPAB). It was qualitative research that employed a purposive sampling technique in determining the study participants. The main participants were twenty-three (23) special education teachers and thirteen (13) school principals and community engagement officers from twelve (12) special education schools. Data gathering tools used were in-depth interviews, quick surveys, and observations. A qualitative descriptive approach was utilized in analyzing the data. The results build the evidence that amidst the countrys efforts over the past decades, children with SEND remain susceptible to disaster due to its delayed implementation in special education schools. A huge gap between the compliance of public and private special education units was identified. Implementation of locally adopted CSS was very recent. It was concluded that teachers competence influences mainly its implementation. Challenges were identified including the unavailability of Disaster Prevention and Risk Reduction Education (DPRRE) integrated modules, limited disability-inclusive teaching materials, and teachers limited training and knowledge about Disaster Risk Reduction and Management (DRRM). The findings suggest a necessity to evaluate the quality and suitability of education units compliance with the provisions of the SPAB program policy